Bioanalysis of emixustat (ACU-4429) in whole blood collected with volumetric absorptive microsampling by LC–MS/MS. (September 2015) - Miao, Zhixin; Farnham, James G; Hanson, Glenn; Podoll, Terry; Reid, Michael J
Background: A method to quantify emixustat (an investigational drug agent) in human blood collected using volumetric absorptive microsampling (VAMS) could be more practical for sample collection at sites with limited facilities for processing and storage of plasma.Methods: A LC–MS/MS method was developed and evaluated for accuracy and precision, linearity, carryover, selectivity, recovery, matrix effects, hematocrit effects and stability.Results: Core validation parameters met acceptance criteria within the normal ranges of hematocrit levels for adults (30–55%). Stability of emixustat in blood collected with and without anticoagulant (NaF/KOx) on the VAMS device at ambient, refrigerated and frozen conditions was established.Conclusion: The method has been validated and is suitable for the bioanalysis of emixustat in human blood collected by VAMS.